Seasonal variations and responses to normal activity of the deep body temperature in the Svalbard reindeer (Rangifer tarandus platyrhynchus) - Cuyler, L. Christine; Øritsland, Nils A. (Rangifer, 1986)
Deep body temperature was recorded in two female Svalbard reindeer during summer and winter. The reindeer were subjected to naturally occurring weather, photoperiod and stimuli in outdoor pens on Svalbard. A telemetry system was employed using transmitters ingested into the rumen. Mean deep body temperature was 0.3°C higher in winter and while the animals were lying down. This suggests a different strategy for thermoregulation than that employed by other reindeer subspecies.